2007
DOI: 10.1158/0008-5472.can-07-2821
|View full text |Cite
|
Sign up to set email alerts
|

The Cooked Meat Carcinogen 2-Amino-1-Methyl-6-Phenylimidazo[4,5-b]Pyridine Activates the Extracellular Signal–Regulated Kinase Mitogen-Activated Protein Kinase Pathway

Abstract: During the cooking of meat, mutagenic and carcinogenic heterocyclic amines are formed, the most abundant of which, 2-amino-1-methyl-6-phenylimidazo [4-5-b ]pyridine (PhIP), induces tumors of the prostate, colon, and mammary gland in rats. Humans consuming cooked meat are exposed to PhIP on a daily basis, yet few studies have assessed the effects of PhIP at dietary relevant concentrations. In addition to its genotoxic properties, recent studies have shown that PhIP can activate estrogen receptor-mediated signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…However, it should be noted that PhIP has also been reported to affect cellular pathways by mechanisms that are independent of ERα (Creton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that PhIP has also been reported to affect cellular pathways by mechanisms that are independent of ERα (Creton et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The most prevalent HCA found in meats is 2-amino-1-methyl-6-phenylimidazo [4,5-b]-pyridine (PhIP). Following metabolic activation, PhIP, along with other HCAs, causes the production of DNA adducts and is carcinogenic in rat colon, mammary, and prostate tissues (119)(120)(121). In rodents and cell lines, PhIP has been shown to stimulate signaling pathways resulting in increased cellular proliferation (119,120,122,123).…”
Section: Meat Consumption Genetics and Cancer Riskmentioning
confidence: 99%
“…However, the intake of grilled meat is thought to be related to PCa risk since high-temperature cooking of meat leads to formation of mutagenic heterocyclic aromatic amines (HCA), which have been shown to induce tumours in experimental animal models [3][4] . Cooking at higher temperatures and for longer periods of time both result in formation of more HCA [3][4] . To date, several observational studies have evaluated the association of intake of meat cooked at high temperature and PCa risk, but results are inconsistent [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…However, experimental studies have shown that levels of PhIP approximating human dietary exposure stimulate cellular signalling pathways and result in increased growth and migration, suggesting a link with the promotion and progression of neoplastic disease 4,12 . One of the reasons for our null-findings might be that the association between HCA intake and PCa risk is modified by different genotypes/polymorphisms in genes encoding for HCA-metabolizing enzymes.…”
Section: Introductionmentioning
confidence: 99%